ANALISIS TINDAK TUTUR FRASA ’PENUH DENGAN ROH KUDUS’ DALAM KISAH PARA RASUL 6–7: STUDI PRAGMATIK TERHADAP KONSTRUKSI OTORITAS SPIRITUAL STEFANUS - Fiona Isaura Talifuddin; Yolanda Nany Palar (DA'AT : Jurnal Teologi Kristen, 2025)
The book of Acts emphasises the active role of the Holy Spirit in the development of the early church. One of the phrases that is explicitly repeated in the narrative is the phrase "Full of the Holy Spirit", especially in the narrative of the character Stephen in Acts 6-7. This study aims to analyse the function of the phrase as part of the author's speech acts in shaping Stephen's character and spiritual authority. Using a qualitative method and a pragmatic linguistic approach, particularly Austin and Searle's theories of speech acts (locution, illocution, and perlocution), this study will explore how the phrase functions not only as a literal description, but also as the author's communicative and rhetorical strategy. The research shows that the repetition of the phrase strategically constructs the image of Stephen as a figure who acts on the basis of divine authority, while leading historical and contemporary readers to reinterpret the source of true spiritual authority. Thus, this study shows how the choice of diction in the Bible has played an active role in shaping the reader's view of the character and the narrative dynamics of the text.